Accounting Conservatism and Its Determinants: Evidence from Indonesian Industrials - Reska Prahasini Sekarwesma; Ramses Pakpahan; Nico Alexander (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2025)
Purpose – This study aims to obtain empirical evidence on the influence of Cash Flow, Leverage, Firm Size and Managerila Ownership on Accounting Conservatism. Design/methodology/approach – This study uses quantitative research. The sample in this study consist of 16 companies in the industrials sector listed on the Indonesia Stock Exchange from 2019 to 2023. The analysis technique used to test the hypothesis was panel data regression analysis using Eviews 9 software. Findings – The results of this study found that Cash Flow has a positive effect on Accounting Conservatism, as does Leverage. Firm Size has a negative influence on Accounting Conservatism, while Management Ownership has no influence on Accounting Conservatism. Research limitations/implications – This study discusses Accounting Conservatism and other factors such as Cash Flow, Leverage, Firm Size and Managerial Ownership that focus on industrial sector companies. This study uses the Accounting Conservatism (CONACC) model as a measurement of Accounting Conservatism.